(untitled) (Research, Society and Development, 2021)
To analyze the pathophysiological aspects of lupus mastitis (LM), clinical presentation, epidemiology, radiological and histological findings, and treatment, to disseminate it to the academic community and draw attention to this pathology as one of the differential diagnoses in the management of breast lesions in males, especially in the case of breast cancer in men. A literature review was done by searching scientific studies in the PubMed / Medline, Scopus, Scielo, Embase, Web of Science, and Google Scholar databases. Relevant scientifically validated studies related to lupus mastitis in men were selected. The analysis, review and selection of articles carried out in pairs, blindly and separately, based on the reading of the title and abstract, with a third reviewer in case of disagreement. The LM should be suspect in patients known to have lupus erythematosus who present painful breast nodules associated with skin changes. However, LM can be the initial manifestation of lupus and mimic, both clinically and imaging, malignant neoplasms. The histopathological diagnostic criteria are well-established, finding mainly hyaline fat necrosis and lymphoplasmacytic infiltrate. Treatment must be drug-based as invasive procedures can exacerbate the injury. Due to physiological and anatomical aspects, this condition can appear and evolve differently in men. The knowledge of this pathology is necessary to carry out the correct approach since the non-identification of the disease and its erroneous management can lead to complications and irreversible sequelae to the patient.